Are We on the Same Page? Family and Museum Staff Perceptions of Engagement and Learning. Issue 2 (3rd July 2019) - Brown, Robert; Jeanneret, Neryl; Andersen, Jennifer
Abstract: Museums are designed to engage families with young children with a welcoming, safe and stimulating environment and museum staff are central to achieving this mission. What staff know about and how they interact with young children and their parents, however, is rarely investigated. This article presents research involving staff and families interacting in a large city museum. The research sought to document and compare a sample of family and staff views and experiences, with the findings showing a positive alignment of views in relation to goals, engagement and learning. Perceptions of if, when and how staff should interact with families are varied and contextualized, highlighting how staff have to be aware of and attuned to attuned to the interests and needs of families.